Collectiesite Frans Hals Museum - Frans Hals Museum (2006)
[Dt.:] Über die Website ist die Sammlung des Frans Hals Museums recherchierbar. - [Engl.:] Web site of the Frans Hals Museum with information to the collection, history and exhibitions of the museum. You can search the collection online.